SARS-CoV-2 infection decreases cardiorespiratory fitness and time-trial performance even two months after returning to regular training - Insights from a longitudinal case series of well-trained kayak athletes - Shengji Deng; Mingyue Yin; Zhili Chen; Jianfeng Deng; Zhenyu Wang; Yuxi Li; Mengde Lyu; Boyi Zhang; Shaoqiang Zhu; Shenggui Hu; George P. Nassis; Yongming Li (Elsevier, 2024)
Objective: The aims of this study were to examine the effect of SARS-CoV-2 infection on cardiorespiratory fitness (CRF) and time-trial performance in vaccinated well-trained young kayak athletes. Methods: This is a longitudinal observational study. Sixteen (7 male, 9 female) vaccinated kayakers underwent body composition assessment, maximal graded exercise test, and 1000-m time-trial tests 21.9 ± 1.7 days before and 66.0 ± 2.2 days after the SARS-CoV-2 infection. The perception of training load was quantified with Borg's CR-10 scale before and after the infection return to sport period. Results: There were significant decreases in peak oxygen uptake (−9.7 %; effect size [ES] = 1.38), peak oxygen pulse (−5.7 %; ES = 0.96), and peak heart rate (−1.9 %; ES = 0.61). Peak minute ventilation, and minute ventilation/carbon dioxide production slope were unchanged after infection compared to the pre-infection values. In the entire 1000-m, the impaired tendencies were found in completion time, mean power, and mean speed (−2.4 to 1.2 %; small ESs = -0.40 to 0.47) as well as significant changes in stroke rate and stroke length (−4.5 to 3.7 %; ESs = -0.60 to 0.73). Conclusion: SARS-CoV-2 infection decreased CRF and time-trial performance even two months after return to regular training in vaccinated athletes.